Barriers to Information Sharing among Humanitarian NGOs; A Case of Jordan - Saada, Raeda Jamal; Abu Taleb, Yara; Nimer, Nabil (International Journal of Supply Chain Management, 2019)
The study aims to identify the barriers in information sharing among humanitarian NGOs, providing educational services for Syrian refugees in Jordan.The study has used qualitative exploratory case study through semi-structured interviews. The interviews were conducted with project managers, coordination officers, and supply managers in their offices in Amman. The results were analysed based on the interviews, conducted among employees. Different barriers were evaluated through the interviews including information availability, internet issues, confidentiality and privacy, the commitment of partners and managemnt, security issues, language barrier, quality of information, corruptio, and culture and tradition. The effectiveness of information systems in supply chaim management leads to incentive misalignment, under-optimal decisions, and difficulties of refugeed demand uncertainty. The information technology facilitates efficient supply chain because of associated advantages, including knowledge and best practices to ensure effective performance.